A new anisophyllous species of Miconia (Melastomataceae: Miconieae) from the Coastal Cordillera in northern Venezuela - Michelangeli, Fabián A.; Meier, Winfried (Phytotaxa, 2013)
Miconia longidentata, a new species of Melastomataceae, Miconieae, from the Coastal Cordillera in northern Venezuela is described. This species is known from cloud and mid elevation forests in the Waraira Repano National Park (formerly known as Ávila National Park). Miconia longidentata is characterized by sessile to sub-sessile, dimorphic leaves, short axillary inflorescences, and four-merous flowers with long calyx teeth. By its character combination Miconia longidentata would have been described as Clidemia, but it is here described in Miconia due to ongoing taxonomic realignments in the Miconieae. The new species is compared to putative relatives, and a list of anisophyllous species traditionally placed in Clidemia is provided. A list of species of Melastomataceae endemic to the Coastal Cordillera in northern Venezuela is also included.